Characteristics influencing the historical performance of U.S. mutual funds - Jung, Young Hoon (My University, 2020)
This study examines variables influencing mutual fund performance. Data were collected from U.S. 181 equity mutual funds during the bull market from 2009 to 2018. The overall object of this study is to determine how funds’ characteristics, risks, and managerial factors are related with 10-year time weighted average return. Using correlation and regression analysis, the results show that asset size and turnover ratio are not statistically significant factors for fund performance. Sales charges and expenses are highly negatively correlated; management tenure and management style, whether team or single management, does not impact on fund return over the examination period. A fund managers’ MBA education does not produce extra return. It is also found that the risks and performance are statistically significantly related. Alpha, beta, skewness, kurtosis, the Sharpe ratio and Treynor impact on funds’ return positively but standard deviation does not. Evaluation metrics are used to examine if regression models can predict 2019 return (out-of-sample performance). It is revealed that the historical data does not explain future returns well. Overall, the results suggest that past performance on mutual funds does not predict future returns well. This is consistent with the weak form of market efficiency.
Keywords: Mutual Funds; Treynor Ratio; Sharpe Ratio; Risk; Performance